Bacteria encapsulation and rapid antibiotic susceptibility test using a microfluidic microwell device integrating surface-enhanced Raman scattering. Issue 14 (16th June 2020) - Huang, Hsiu-Kang; Cheng, Ho-Wen; Liao, Cheng-Chieh; Lin, Shang-Jyun; Chen, Yi-Zih; Wang, Juen-Kai; Wang, Yuh-Lin; Huang, Nien-Tsu
Abstract : We developed a microfluidic microwell device integrating SERS substrate for an efficient bacteria encapsulation and enrichment followed by in situ SERS-AST measurement, which can potentially apply for high throughput and multi-parallel AST. Abstract : The antibiotic susceptibility test (AST) is a general laboratory procedure for bacterial identification and characterization and can be utilized to determine effective antimicrobials for individual patients. Due to the low bacterial concentration, conventional AST usually requires a prolonged bacterial culture time and a labor-intensive sample pretreatment process. Therefore, it cannot perform timely diagnosis or treatment, which results in a high mortality rate for seriously infected patients. To address this problem, we developed a microfluidic microwell device integrating surface-enhanced Raman scattering (SERS) technology, or the so called the Microwell-SERS system, to enable a rapid and high-throughput AST. Our results show that the Microwell-SERS system can successfully encapsulate bacteria in a miniaturized microwell with a greatly increased effective bacteria concentration, resulting in a shorter bacterial culture time. By attaching a microchannel onto the microwell, a smooth liquid and air exchange can purify the surrounding buffer and isolate bacteria in an individual microwell for independent SERS measurement. For proof-of-concept, we demonstrated a 2 h AST on susceptible and resistant E. coli and S. aureus with a concentration of 10 3 CFU mL −1 in the Microwell-SERS system, whereas the previous SERS-AST method required 10 8 CFU mL −1 bacterial suspension droplets dispensing on a SERS substrate. Based on the above features, we envision that the Microwell-SERS system could achieve highly sensitive, label-free, bacteria detection and rapid AST to enable timely and accurate bacterial infection disease diagnosis.